Symptom severity of depressive symptoms impacts on social cognition performance in current but not remitted major depressive disorder - Air, Tracy; Weightman, Michael J.; Baune, Bernhard T. (Frontiers in Psychology, 2015)
The aim of the study was to investigate the social cognitive functioning of participants with major depressive disorder when compared with healthy controls, and to assess the impact of symptom severity and affective and somatic symptom clusters on social cognition. One hundred and eight adult patients with depression (66 remitted and 42 current) and 52 healthy controls were assessed using the Wechsler Advanced Clinical Solutions: Social Perception Subtest, measuring facial affect recognition in isolation and in combination with prosody and body language interpretation. While no associations between the diagnostic status (MDD vs controls) and any of the social cognition measures were found, severity of depressive and anxious symptoms predicted performance on all social cognition subscales in currently depressed participants, controlling for age, gender, education and psychotropic medication. Moreover, in the current MDD group, an affective depressive symptom cluster was inversely related to performance on the more complex ACS Pairs and Prosody tasks, while a somatic symptom cluster was inversely related to ACS Affect Recognition and Total scores. In contrast, there were no associations between symptom severity or symptom clusters and the WAIS ACS in remitted depression participants. Given the state like nature social deficits in this study, these impairments may cause problems with day to day functioning and have implications in targeted therapeutic interventions.